2023
DOI: 10.1177/20556683231171840
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for at-home upper-limb rehabilitation technology following stroke: Perspectives of stroke survivors and therapists

Abstract: Introduction This study investigated the needs of stroke survivors and therapists, and how they may contrast, for the design of robots for at-home post stroke rehabilitation therapy, in the Ontario, Canada, context. Methods Individual interviews were conducted with stroke survivors ( n = 10) and therapists ( n = 6). The transcripts were coded using thematic analysis inspired by the WHO International Classification of Functioning, Disability, and Health. Results Design recommendations, potential features, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The device offers two degrees of freedom: An actuated one for grasping as well as haptic rendering, and a passive one for pronosupination movements. Meeting the stringent criteria for home rehabilitation devices is challenging (Chen et al, 2019 ; Forbrigger et al, 2023b ). It has been shown that usability and users' perceptions of assistive devices and rehabilitation technology for home use substantially influence their long-term utilization (Biddiss and Chau, 2007 ; Sivan et al, 2014 ; Sugawara et al, 2018 ; Ciortea et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The device offers two degrees of freedom: An actuated one for grasping as well as haptic rendering, and a passive one for pronosupination movements. Meeting the stringent criteria for home rehabilitation devices is challenging (Chen et al, 2019 ; Forbrigger et al, 2023b ). It has been shown that usability and users' perceptions of assistive devices and rehabilitation technology for home use substantially influence their long-term utilization (Biddiss and Chau, 2007 ; Sivan et al, 2014 ; Sugawara et al, 2018 ; Ciortea et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through interviews with both groups, key design recommendations, potential features, and barriers emerged, highlighting the importance of incorporating the insights of survivors of stroke into home environments and therapists’ expertise in therapy methodology and safety. The findings underscored the necessity of tailored design approaches that consider a range of impairments, incorporate household items, and address individual motion requirements [ 15 ]. Another study [ 16 ] investigated Swedish health care professionals’ use of ICT for person-centered stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%